Arbitrary Power Splitting Couplers Based on 5x5 Multimode Interference Structures for VLSI Photonic Integrated Circuits - Thanh, Le Trung; Truong, Cao Dung (VNU Journal of Science: Mathematics - Physics; Vol 27 No 3, 2011)
Abstract. Chip level optical links based on VLSI photonic integrated circuits have been proposed to replace metal electrical data paths in cases where high frequencies make electrical traces impractical. This is especially relevant to high-speed clock signals as silicon CMOS circuit technology is scaled higher in speed to the GHz range and beyond. In this paper, new structures of optical couplers and power taps based on 5x5 multimode interference structures using CMOS technology are presented. The proposed devices can be useful for all-optical interconnects, clock distribution and many other all-optical processing applications. The transfer matrix method and the 3D Beam Propagation Method (3D BPM) are used to optimize the proposed devices. Keywords: Integrated optics, multimode interference (MMI) couplers, CMOS technology, all-optical processing